A study of the properties of an oil-based drilling fluid with using emulsifier EM-4; Journal of Economics and Social Sciences; № 10 - Yakimenko E. V. Elena Vladimirovna; Fenzel A. Andrey; Sukharev M. Maxim; Chernykh T. Tatyana (Экономические науки, 2017)
Title screen